The Effect of Workload and Commitment on Online Motorcycle Taxi Drivers’ Performance - Hartono Hartono (Jurnal Ilmu Manajemen Advantage, 2023)
The community daily life is inseparable from the need of transportation facility. The need of transportation seems to be a certain business opportunity for some people. Lumajang Go is a technology company established in Lumajang regency that provides public transportation service application include 2-wheeled and 4-wheeled motorized vehicles. The objective of this research is to determine the effect of workload and commitment on the online motorcycle taxi drivers’ performance of Lumajang Go in Lumajang with a sample of 30. The method of this study is using multiple regression analysis technique. The result of this study shows that workload has no significant effect on drivers’ performance, commitment has significant effect on drivers’ performance while workload and commitment have significant effect on drivers’ performance simultaneously.